Improving blacksmith safety through protective equipment education and occupational health and safety program support - Ida Ayu Made Sri Arjani; Cok Dewi Widhya Hana Sundari; Nyoman Mastra; Burhannuddin Burhannuddin (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Pande Besi or blacksmith craftsmen, is one of the small industries that has developed in Tabanan Regency, Bali Province. Blacksmith craftsmen are exposed to a hot, dusty, and smoky environment, posing potential hazards to occupational health and safety. They typically work on the floor with makeshift seats, adopting non-ergonomic postures that can lead to musculoskeletal complaints such as pain in the back, waist, neck, shoulders, and buttocks. The purpose of this service activity is to educate blacksmith craftsmen on the importance of using Personal Protective Equipment (PPE) and maintaining proper working postures to prevent accidents and occupational diseases. This activity involves training and mentoring, targeting 30 individuals, focusing on the use of PPE, and improving work attitudes to reduce musculoskeletal complaints and occupational diseases. Results from 30 respondents showed that before counseling and assistance, the majority of the blacksmith craftsmen's knowledge was in the sufficient category (46.67 percent). After counseling, 90 percent of the respondents' knowledge was in the good category. Regarding work attitudes, before mentoring, the highest value was less than 70 percent, while after mentoring, 93.33 percent were categorized as having a good work attitude. The impact of this activity is an increase in knowledge and improvement in the work attitudes of blacksmith craftsmen in Tabanan Regency.